Incremental Predictive Value of Carotid Inflammation in Acute Ischemic Stroke. Issue 1 (January 2015) - Toutouzas, Konstantinos; Benetos, Georgios; Drakopoulou, Maria; Deligianni, Christina; Spengos, Konstantinos; Stefanadis, Christodoulos; Siores, Elias; Tousoulis, Dimitrios
<x xml:space="preserve">Abstract</x> Background and Purpose— Microwave Radiometry (MWR) allows in vivo noninvasive assessment of internal temperature of tissues. The aim of the present study was to evaluate in patients with ischemic stroke and bilateral carotid plaques (1) whether ipsilateral carotid arteries exhibit higher temperature differences (ΔT), as assessed by MWR; (2) the predictive accuracy of MWR in symptomatic carotid artery identification. Methods— Consecutive patients with recent acute anterior circulation ischemic stroke because of large artery atherosclerosis were included in the study. Carotid arteries of all patients were evaluated by carotid ultrasound and MWR. Results— In total, 50 patients were included in the study. Culprit carotid arteries had higher ΔT compared with nonculprit (0.93±0.58 versus 0.58±0.35°C; P<0.001). The addition of ΔT to a risk prediction model based only on ultrasound plaque characteristics increased its predictive accuracy significantly (c-statistic: 0.691 versus 0.768; Pdif=0.05). Conclusions— Culprit carotid arteries show higher thermal heterogeneity compared with nonculprit carotid arteries in patients with acute ischemic stroke and bilateral carotid plaques. MWR has incremental value in culprit carotid artery discrimination.